ANALISIS LITERATUR TERHADAP KEBIJAKAN IMPLEMENTASI PENDIDIKAN INKLUSIF PADA SATUAN PENDIDIKAN DI KOTA PEKANBARU - Ringgi Rahmat Fitra; Yodinasya Trixie Belia; Fiyola Triana Eldiva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Inclusive education is a strategic approach within the education system that guarantees equal learning opportunities for all students, including those with special needs. Although Indonesia’s national policies have laid out the framework for inclusive education through various regulations, its implementation at the regional level still faces a number of significant challenges. This study aims to systematically analyze inclusive education policies in the city of Pekanbaru through a literature review approach. Data were drawn from academic journals, scholarly books, and both national and local policy documents, such as Regional Regulation of Pekanbaru City No. 2 of 2023 and Mayor’s Decree No. 713 of 2017. The findings reveal a clear gap between normative policy and actual practice in schools. This gap is reflected in the inconsistent understanding of inclusive principles among teachers, the limited availability of training, and the inadequate presence of Special Needs Support Teachers (GPK). Additionally, the absence of detailed technical guidelines and a reliable monitoring system from local authorities has further hindered implementation. Therefore, policy reform at the regional level is essential focusing on institutional capacity building, investment in human resources, and the development of a continuous evaluation mechanism to ensure that inclusive education is implemented in a meaningful and equitable manner.